Effect of stirring speeds on biodiesel yield using an innovative oscillatory reactor and conventional STR (A comparative study). (1st October 2022) - Khelafi, Mostefa; Djaafri, Mohammed; Kalloum, Slimane; Atelge, M.R.; Abut, Serdar; Dahbi, Abdeldjalil; Bekirogullari, Mesut; Atabani, A.E.
Graphical abstract: Highlights: An oscillating reactor to improve the biodiesel yield is innovated. The rod-crank principle was used to generate an oscillating motion. At low stirring speed, the oscillating reactor was more efficient with both the heterogeneous and the homogeneous catalysts. At higher speeds, the conventional reactor was more efficient when using the heterogeneous biocatalyst. In contrary, the oscillating reactor was more efficient when using the homogeneous catalyst. Low speed requires low energy and thus makes the oscillating reactor more cost-effective. Abstract: This paper aims to study the effect of stirring speed on biodiesel yield using an innovative oscillating reactor compared to the conventional stirring tank reactor. The efficiency of the invented reactor was compared with the conventional system, employing two catalysts (a homogeneous catalyst and a heterogeneous bio-catalyst). The obtained results showed that under low agitation speed of 50 rpm, the invented oscillating reactor is more efficient than the conventional system with a biodiesel yield of 93% compared to 90.13% using the heterogeneous catalyst and 93.53% compared to 92.7% using the homogeneous catalyst respectively. As for the higher stirring speeds, the conventional system was found to be slightly more efficient than the oscillating reactor when using the heterogeneous biocatalyst (96.03% against 94.42%) while the contrary was observed when using the homogeneous catalyst (94.43% against 95%). However, this slight increase in the biodiesel yield at higher speeds results in increasing production costs. This indicates that biodiesel production using the innovative oscillating reactor at low speeds is more economically viable. The characteristics of the produced biodiesel using the invented reactor were in agreement with the ASTM D6751 biodiesel standards. Moreover, a two-way ANOVA analysis was conducted to compare between groups that have been split on two independent variables as reactor type and stirring speed. The statistical analysis proved that the invented oscillating reactor performs better when using heterogeneous catalysts at low stirring speed levels. This study suggests that the biodiesel yield of the innovative reactor can be further enhanced by introducing a baffle system which provides a relatively larger contact surface area. Similarly, synthesis of other heterogeneous bio-catalysts derived from the date seed of another date palm cultivar can be tested to further improve the biodiesel yield.